PENGARUH PROFITABILITY, LIQUIDITY, DAN LEVERAGE TERHADAP EARNINGS QUALITY DENGAN MODERATOR FIRM SIZE - Maghveera Aslam; F.X. Kurniawan Tjakrawala (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of profitability, liquidity, and leverage on earnings quality with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. This research used 65 samples and 325 data from manufacturing companies selected by purposive sampling method. The data in this research were inputted and calculated using the Microsoft Excel program and processed using the Eviews 10 program. The results of this study indicate that profitability and leverage have a significant positive effect on earnings quality, while liquidity has no significant effect on earnings quality. Firm size as a moderating variable has a negative effect of profitability on earnings quality.